Penguasaan Strategi Meminta Pada Laki-Laki Remaja Usia 18-20 Tahun Dalam Aplikasi Bumble: Kajian Psikolinguistik - Wahdatunnisa, Ratu Hilma; Utami, Silvia; Putra, Dona Aji Karunia (Madani: Jurnal Ilmiah Multidisiplin, 2024)
One of the online dating-based applications that is focused on in this study is the Bumble application. This study discusses how to master the strategy of asking teenage boys aged 18-20 years in the Bumble application with the aim of meeting face to face with their interlocutors. This research uses descriptive qualitative method. Based on the results of this study, there are 10 strategies used by 10 teenage boys aged between 18 and 20 years in asking to meet the other person. As for mastering the asking strategy spoken in the Bumble application, there are several forms of sentences used, such as: declarative, interrogative, and imperative sentences. Then use speech acts in the form of offers, orders, and praise. So it can be concluded that there is 1 male teenager aged 18 using imperative sentences with directive speech acts (commands), 3 male adolescents aged 19 using interrogative sentences and declarative sentences with commissive speech acts (offers), and 6 male adolescents aged 20 years use declarative sentences, interrogative sentences, and imperative sentences using commissive (offer) and expressive (praise) speech acts. And all the strategies carried out by 10 teenage boys aged 18-20 years use indirect speech.